Learning theories, motivation, and distance education - Torun, Fulya; Güler, Tülay Dargut; Şanal, Seda Özer (IGI Global, 2021)
Education is a related structure that can never be defined or even exist as separate from human beings. Behavioral, cognitive, and constructivist paradigms each try to explain learning with different concepts and principles. Well, did these theories survive the distance education process? Let's say each theory survived in distance education. Then the following questions come up: What does motivation mean for these theories? How do these theories make the motivational structure sustainable in distance education? Aiming at a comprehensive discussion of these questions, the chapter offers many answers and brings many different questions to mind. This chapter will guide instructors and instructional designers to design efficient learning opportunities for learners. © 2021, IGI Global.